An Analysis Basic Strategy of Verbal Humor found In Ellen DeGeneres Monologue Season 17,2019 : Pragmatic Approach study - Alvina faula (MEDIOVA: Journal of Islamic Media Studies, 2022)
Abstract : Language is not only a means of communication between humans; however, it can convey funny expressions known as humor. Everyone likes something fun and funny. In entertainment, humor has developed; thus, physically offensive humor decreases and proceeds to verbal humor, especially on talk shows. As one of America's famous comedy talk shows, Ellen DeGeneres Talkshow successfully maintains its fame and verbal humor. Using a Pragmatic context approach, this study uses the theory of Victor Raskin's Three Major Elements of Humor, which consists of Incongruity, Superiority, and Release/Relief. This study aims to determine the types of humor elements that influential in Ellen Monologue Season 17, 2019, entitled "A Look Back at Best Moment and Favorite Season 17,2019â€. The research method used in this research is descriptive-qualitative for analysis of data transcript. This study found that the Ellen DeGeneres talk show has three strong elements of humor as a strategy to trigger audienceâ€™s laughter, including Incongruity, Superiority, and Release. This three elements can work well together and have succeeded elements to significantly influence Ellen DeGeneres talk show. A jokes become accurate and precise when this element of humor is used.